Patterns of mortality in domesticated ruminants in Ethiopia - Innocent, Giles T.; Vance, Ciara; Ewing, David A.; McKendrick, Iain J.; Hailemariam, Solomon; Nwankpa, Veronica R.; Allan, Fiona K.; Schnier, Christian; Peters, Andrew R. (Frontiers in Veterinary Science, 2022)
Background: In Ethiopia, there are limited data on the causes of ruminant mortality and reproductive losses which is hampering the development of interventions to improve livestock health. The present study aimed to establish the causes and magnitude of mortality and reproductive losses in cattle, sheep and goats across all smallholder production systems in Ethiopia. Methods: The study, consisting of three data sources, was conducted to collect data on mortality and reproductive losses in cattle, sheep and goats. Nine regional states; Afar, Amhara, Benishangul Gumuz, Gambela, Harari, Oromia, Southern Nations, Nationalities, and Peoples’ Region, Somali, and Tigray were surveyed, as well as the city administrations of Dire Dawa and Addis Ababa. Questionnaire surveys were conducted with farmers and key stakeholders, as well as data collected from regional diagnostic laboratories. Data from the Living Standards Measurement Study were also included. Generalised linear mixed and hurdle models were used for data analysis, with results summarized using predicted outcomes. Results: Analyses indicated that most herds experienced zero mortality and reproductive losses, with rare occasions of larger losses. Diseases causing deaths varied greatly both geographically and over time. There was little agreement between the different datasets. While the models aid the understanding of patterns of mortality and reproductive losses, the degree of variation observed limited the predictive scope. Conclusions: The models revealed some insight into why mortality rates are variable over time and are therefore less useful in measuring production or health status, and it is suggested that alternative measures of productivity, such as young stock mortality, would be more stable over time and likely more indicative.